2012
DOI: 10.1016/s0030-6657(12)70761-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategie radzenia sobie ze stresem u osób dorosłych postlingwalnie ogłuchłych korzystających z implantu ślimakowego, w porównaniu z populacją ogólną słyszących

Abstract: Postlingually deafened CI patients more often use the ineffective coping strategies. This tendency becomes stronger with the time lapse from the cochlear implantation and is more frequent in women, which corresponds with the data on both the considerably worse mental health of the postlingually deafened people compared to the general population and the deterioration of the mental, social and physical functioning with the lapse of time from the implantation. The standing availability of the psychological suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
20

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 11 publications
1
5
0
20
Order By: Relevance
“…In other words, a significant drop in efforts required to master a situation was observed after CI. This finding is consistent with Kobosko et al (2012), who found that 78 post-lingually deafened adult patients employed less active coping strategies and more avoidance following CI.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, a significant drop in efforts required to master a situation was observed after CI. This finding is consistent with Kobosko et al (2012), who found that 78 post-lingually deafened adult patients employed less active coping strategies and more avoidance following CI.…”
Section: Discussionsupporting
confidence: 92%
“…Logopedzi z kolei spostrzegają pacjentki jako osoby mające większą trudność w zakresie identyfikacji dźwięków otoczenia i dźwięków mowy o wysokiej częstotliwości oraz wskazują je jako osoby bardziej potrzebujące treningu słuchowego. Być może uzyskane rezultaty wiążą się z większymi umiejętnościami adaptacyjnymi mężczyzn do korzystania z nowego urządzenia, jakim jest CI, a także z wykorzystywaniem efektywniejszych sposobów radzenia sobie w sytuacjach trudnych, co wykazały badania prowadzone z udziałem dorosłych pacjentów postlingwalnie ogłuchłych korzystających z CI [Kobosko, Pankowska, Skarżyński 2012]. W naszej opinii, korzyści uzyskiwane z użytkowania CI zależą od bardzo wielu czynników, a płeć może być jednym z nich.…”
Section: Dyskusjaunclassified
“…Los sordos postlocutivos rara vez utilizan estrategias eficaces tales como el afrontamiento activo, planificación y humor, y tienden más al uso a la negación. En algunos estudios se muestra que las personas implantadas presentan una salud mental y social peor, además de peor funcionamiento físico (Kobosko, Pankowska, & Skarżyński, 2012). Aunque otros estudios concluyen que el bienestar psicológico mejora gracias al uso del dispositivo (Rembar, Lind, Arnesen & Helvik, 2009).…”
Section: Factores Relacionados Con La Personaunclassified
“…Faltan por realizar estudios que se centren en las actitudes y las percepciones del implante coclear en los diferentes contextos. La disponibilidad permanente de apoyo psicológico para estos pacientes es esencial, así como el conocimiento de sus problemas (Kobosko et al, 2012). Hay consultas para la evaluación de la pérdida, pero no hay demasiados servicios para hacer frente a las necesidades psicosociales, solamente para las audiológicas (Claesen & Pryce, 2012).…”
Section: Factores Relacionados Con La Personaunclassified
See 1 more Smart Citation